Interrelationships Among Vitamin D Status and Body Composition in Mother-Infant Dyads. (29th May 2020) - Razaghi, Maryam; Vanstone, Catherine; Sotunde, Olusola; Gharibeh, Nathalie; Wei, Shu Qin; McNally, Dayre; Rauch, Frank; Jones, Glenville; Kimmins, Sarah; Weiler, Hope
Abstract: Objectives: To explore the associations between postpartum maternal vitamin D status and body composition to neonatal serum 25-hydroxyvitamin D (25(OH)D) and body composition. Methods: Healthy mothers and term-born infants of appropriate size for gestational age were recruited from Greater Montreal (March 2016 through March 2019). The present analysis includes data from mothers and infants ( n = 144). Maternal characteristics and lifestyle factors were surveyed and newborn capillary blood samples were taken within 36 h of delivery to assess vitamin D status using total serum 25(OH)D (Liaison, Diasorin). Maternal and infant anthropometry and body composition (Dual-energy X-ray absorptiometry) and maternal serum 25(OH)D were measured within 1 mo postpartum. Mothers were classified into 2 groups (group 1: ≥50 nmol/L; group 2: <50 nmol/L). Data were analyzed descriptively (mean ± SD or n (%)) and using a mixed model with Tukey post hoc tests accounting for neonatal sex, gestational age, season, family income, maternal age, education, and race. Correlation tests were used to identify linear relationships between continuous variables. Results: Neonates (85 males, 59 females) were 39.7 ± 1.0 wk GA and 3393 ± 363 g at birth. Mothers (32.1 ± 4.5 years) in group 1 had considerably higher serum 25(OH)D concentrations compared to mothers in group 2 (80.3 ± 22.0 n = 96 vs. 38.7 ± 9.0 n = 48, nmol/L, P < 0.0001). Moreover, maternal serum 25(OH)D concentrations were positively associated with their % whole body lean mass ( r = 0.28, P = 0.0009) and inversely associated with their % whole body fat mass ( r = −0.25, P = 0.003). At birth, infants of mothers in group 1 had higher serum 25(OH)D concentrations compared to infants in group 2 (51.0 ± 18.1 vs. 27.0 ± 12.0 nmol/L, P < 0.0001), and were correlated with maternal 25(OH)D ( r = 0.74, P < 0.0001). Maternal lean body mass and lean mass index (LMI) (kg/m2) explained some positive variations in infant lean body mass and LMI (Estimate = 0.01, P = 0.004; Estimate = 27.7, P = 0.04). Conclusions: Higher maternal vitamin D status is associated with higher neonatal vitamin D with possible implications to neonatal lean body mass. This study reinforces the importance of ensuring adequate maternal-fetal transfer of vitamin D. Funding Sources: Canadian Institutes of Health Research.